KAJIAN LOADING-UNLOADING CRUDE OIL DARI PLATFORM KE FSO ABERKHA - Zulfaidah Ariany (POLITEKNIK NEGERI BENGKALIS, 2019)
FSO (Floating Storage & Offloading), is a floating / ship building that is used as a place to store crude oil. This crude oil is usually from FPS or FPU which is transferred to the FSO through a submerged turret loading (STL) system, then exported/offloaded to the tanker shelter through flexible hoses on the back of the FSO. The existence of FSO greatly benefits the oil industry, since it can be placed as close to the drilling area which is generally offshore. The method of loading ships that arrive can be done in various ways, including STS (ship to ship), Tandem (stern mooring), and SPM (single point mooring). A ship used to store oil is only referred to as a floating storage and offloading vessel (FSO). The results of the analysis show that the efficiency of pump usage has an effect on the fluid flow rate, it’s evident from the use of pumps to move crude oil in a pipeline resulting in an image with the highest stress value reaching 89 Pa at an efficiency value of 98%. criteria for safety factors that are allowed.